2016
DOI: 10.1039/c6tb00266h
|View full text |Cite
|
Sign up to set email alerts
|

Smart pH-responsive and high doxorubicin loading nanodiamond for in vivo selective targeting, imaging, and enhancement of anticancer therapy

Abstract: Nanodiamond as a carrier for transporting chemotherapy drugs has emerged as a promising strategy for treating cancer. However, several factors limited its extensive applications in biology, such as low drug loading, easily cluster and a high drug loss under physiological environment. In this work, to ensure high drug capacity and low drug leakage in physiological conditions, and especially ensure to be delivered to tumor region, a smart pH-responsive drug delivery system was designed and prepared by DOX adsorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 53 publications
1
11
1
Order By: Relevance
“…It was reported that when the MNDDS enter to the cell, Dox release could be affected partly by the endosomal and lysosomal lumen whose pH is maintained in a range of 6.5 to 4.5 [48] . Our results are consistent with those reported by Li et al., [49] the amount of Dox released from the Dox‐PEGylated nanodiamond system at acid pH (pH 5.5) faster than at neutral pH conditions (pH 6.5 or pH 7.4).…”
Section: Resultssupporting
confidence: 93%
“…It was reported that when the MNDDS enter to the cell, Dox release could be affected partly by the endosomal and lysosomal lumen whose pH is maintained in a range of 6.5 to 4.5 [48] . Our results are consistent with those reported by Li et al., [49] the amount of Dox released from the Dox‐PEGylated nanodiamond system at acid pH (pH 5.5) faster than at neutral pH conditions (pH 6.5 or pH 7.4).…”
Section: Resultssupporting
confidence: 93%
“…Negligible cytotoxicity has been demonstrated for the NDs used in this work (data not shown); note, that low or no cytotoxicity has been demonstrated before for different kinds of NDs elsewhere [27,50,55,60]. The NDs’ surface can be functionalized and modified with molecules of interest for interaction for further bio-applications [24,28,61].…”
Section: Resultsmentioning
confidence: 81%
“…Understanding the NP interaction with the skin is important for topical, local drug delivery, including nanoparticle-provided delivery of drugs [20,22], such as delivery via the topical application of a nanoparticle-drug system with slow controllable drug release [23]. Among the nanomaterials with demonstrated facilities of controlled drug release, nanodiamonds (NDs) are a promising candidate in the development of multiple applications [24,25]. However, the potential applications of NDs in transdermal drug delivery, as well as other theranostic applications, will depend on understanding the ND interaction with the skin and on the ability to detect and visualize the interaction with the skin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach to combine doxorubicin with an additional molecule was shown by Li et al They attached doxorubicin onto diamond particles that were coated with polyethylene glycol (PEG). PEG is well known for its excellent properties when it comes to suppressing immune responses.…”
Section: Diamonds For In Vivo Applicationsmentioning
confidence: 99%